Linguistic attitudes towards the indicative mood past shown by students from Universidad Nacional Mayor de San Marcos - Robles Muñoz, Mirella Alexandra (2019)
This article describes the linguistic attitudes shown by Spanish speakers from Lima -students at the Universidad Nacional Mayor de San Marcos (UNMSM)- with respect to the past in indicative mood. For this purpose, the application of the following methods is taken into account: the survey, the sociolinguistic interview and the Matched-Guise test, in order to obtain the frequency of use of the preterite, to know the linguistic competence and attitudes with respect to the preterite in indicative mood by the students of the UNMSM. It is also intended to test the following hypotheses: UNMSM students do not always use the standard language when using preterites in contexts of partial narratives and direct questions. In addition, UNMSM students have positive attitudes and ideas regarding the use of preterite in its standard variety and negative in its non-standard variety. On the other hand, the justification lies in the fact that the results will provide a clear vision regarding the linguistic attitudes of the Spanish speakers from Lima.